Experimental assessment of warming effects on the architecture and growth of the subalpine species Nothofagus pumilio - Torres, Cristian Daniel; Aparicio, Alejandro Gabriel; Puntieri, Javier Guido; Soliani, Carolina; Stecconi, Marina; Pastorino, Mario Juan (Oxford University Press, 2025)
Global warming can pose a significant threat to forest tree species, particularly those inhabiting subalpine forests in temperate regions. Plasticity and adaptation are essential for the persistence of these forests. Nothofagus pumilio, the dominant tree species at the high-altitude limits of Patagonian temperate forests, is well adapted to cold conditions. To assess its potential responses to global warming, we established a genetic multi-environment field trial across three altitudes, 1200 (the current optimal for N. pumilio in North Patagonia), 800, and 400 m a.s.l., using plants from three provenances. Our hypothesis was that warmer conditions would reduce plant survival and promote the early expression of developmental attributes associated with advanced ontogenetic stages. After three growing seasons from trial planting, we measured survival, growth, and architectural traits. Plant survival and radial growth were lower at warmer, suboptimal sites. Warmer conditions induced the early expression of traits associated with advanced ontogenetic stages, particularly in two provenances, highlighting significant genotype-by-environment interactions. Additionally, plants at intermediate altitudes exhibited reduced height and a less hierarchical trunk structure, suggesting that juvenile growth and architecture in N. pumilio may be affected not only linearly with rising temperatures, but by interactions with stochastic factors, such as episodic frosts, which could operate on warming-induced effects decoupling plants from normal seasonality.